Doughnut-Shaped and Top Hat Solar Laser Beams Numerical Analysis - Miguel Catela (MDPI AG, 2021)
Aside from the industry-standard Gaussian intensity profile, top hat and non-conventional laser beam shapes, such as doughnut-shaped profile, are ever more required. The top hat laser beam profile is well-known for uniformly irradiating the target material, significantly reducing the heat-affected zones, typical of Gaussian laser irradiation, whereas the doughnut-shaped laser beam has attracted much interest for its use in trapping particles at the nanoscale and improving mechanical performance during laser-based 3D metal printing. Solar-pumped lasers can be a cost-effective and more sustainable alternative to accomplish these useful laser beam distributions. The sunlight was collected and concentrated by six primary Fresnel lenses, six folding mirror collectors, further compressed with six secondary fused silica concentrators, and symmetrically distributed by six twisted light guides around a 5.5 mm diameter, 35 mm length Nd:YAG rod inside a cylindrical cavity. A top hat laser beam profile (Mx2 = 1.25, My2 = 1.00) was computed through both ZEMAX® and LASCAD® analysis, with 9.4 W/m2 TEM00 mode laser power collection and 0.99% solar-to-TEM00 mode power conversion efficiencies. By using a 5.8 mm laser rod diameter, a doughnut-shaped solar laser beam profile (Mx2 = 1.90, My2 = 1.00) was observed. The 9.8 W/m2 TEM00 mode laser power collection and 1.03% solar-to-TEM00 mode power conversion efficiencies were also attained, corresponding to an increase of 2.2 and 1.9 times, respectively, compared to the state-of-the-art experimental records. As far as we know, the first numerical simulation of doughnut-shaped and top hat solar laser beam profiles is reported here, significantly contributing to the understanding of the formation of such beam profiles.